Sacituzumab Govitecan: First Approval - Syed, Yahiya Y. (Drugs, 2020)
Sacituzumab govitecan (sacituzumab govitecan-hziy; Trodelvy™) is a Trop-2-directed antibody conjugated to a topoisomerase I inhibitor (SN-38) that is being developed by Immunomedics for the treatment of solid tumours, including breast cancer. In April 2020, sacituzumab govitecan received accelerated approval in the USA for the treatment of adult patients with metastatic triple-negative breast cancer (mTNBC) who have received at least two prior therapies for metastatic disease. Sacituzumab govitecan is undergoing phase III development for breast cancer in the USA and EU, and phase II development for urothelial cancer. It is also being explored for brain metastases, glioblastoma, endometrial cancer and prostate cancer. This article summarizes the milestones in the development of sacituzumab govitecan leading to this first approval for mTNBC.